The carnivalization and polyphony in Ernesto Sábato’s On Heroes and Tombs (1961) - de Taboada, Javier (2023)
The article is based on the approaches of the Russian theorist Mikhail Bakhtin. Bakhtin proposes the concepts of carnivalization and polyphony as central categories of his literary theory. Likewise, in his analysis of Dostoevsky’s work, he affirms that the polyphonic novel is rarely presented in literature, and that this category cannot be applied to any literary work, but that it must comply with certain presuppositions. The article attempts to demonstrate that the Argentine writer Ernesto Sábato’s novel Sobre héroes y tumbas (On Heroes and Tombs) fits this concept due to the carnivalesque world it presents and the multitude of autonomous voices that appear in it. Furthermore, it examines the voices present in the novel by classifying them and explaining their structural importance in the work.